Searching for the Holy Grail among ear drops - Kiełbasa, Justyna; Bil, Katarzyna; Kowalczyk, Agata; Zozula, Natalia; Latała, Aleksandra; Ślesicka, Iga; Rykucka, Aleksandra; Wąs, Marcin; Przestrzelska, Magda; Tomczewska, Zuzanna (Journal of Education, Health and Sport, 2024)
Introduction and aim of the study: Ear wax plays many roles in maintaining ear health, such as cleansing, shielding, and lubricating the external auditory canal. Sometimes, when earwax obstruction occurs, for example as a result of improper hygiene procedures (such as using cotton swabs), it can cause a number of disorders ranging from discomfort to even loss of hearing. In such cases, various methods can be used to remove the cerumen impaction. One of these and also the most commonly used, involves the usage of ear drops, which can contain different active substances (water-based compounds, oil-based compounds, a combination of oil and water-based compounds, and non-water, non-oil solutions). The aim of our study is to present current state of knowledge about effectiveness of various types of ear drops in wax cleaning. Material and methods: Our review is based on the analysis of materials collected in Pubmed”, „Google Scholar” and other scientific articles using keywords: „earwax”, cerumen impaction”, „cerumenolytics”, „ear drops”, „cerumen”, „earwax solvents”, „wax solvents”. Conclusions: Despite numerous studies, the Holy Grail has not been found among ear drops. The majority conducted studies did not show that any of the cerumenolitics were superior to the others in a statistically significant way. The only result that was statistically significant was the one showing a higher effectiveness of 2.5% sodium bicarbonate compared to docusate sodium. Further research is needed.